Converting Operation Database to Star Schema Structure - Mohammed, Mohammed Aal (2010)
Today's, structural data representation has been developed rapidly in term of complexity. Different studies addressed the advantages of employing five star schemas in simplifying and managing the data components based techniques. Moreover, other researchers highlighted the importance of using data warehouse in enhancing the database abilities and handling large amounts of data in different structural representation. Hence, this study aimed to apply the five star schema structures in simplifying the data retrieval process. System development research methodology has been employed in this study for analyzing and developing the proposed system. Result has been conducted based on the using of use test case technique.